Growth Response And Yield Of Bambara Groundnut (Vigna Subterranea (L.) Verdcourt) To Nitrogen Fertilization - Asshobri, Farhaz Sahdi; Tamam, Muhammad Fathan; Widyaningrum, Nadila Gusti Sekar; Saleh, Ismail (Jurnal Agrosci, 2025)
Bambara groundnuts are indeterminate legume plants that resist drought and less fertile land, so they have the potential for cultivation. The yield of bambara groundnut cultivated by farmers in Indonesia is still low. Nitrogen fertilizer is an important element for crop production, but the optimum dose of nitrogen for bambara groundnuts is not yet known. Therefore, this study aims to determine the optimum dose of N fertilization for optimal growth and yield of bambara groundnut plants. The research was conducted from July to October 2024 in Nanggela Village, Mandirancan District, Kuningan Regency. The experimental design used randomized block design (RBD) with six replications. The treatment was a dose of nitrogen fertilizer, namely 0, 100, 200, and 300% of the recommended dose. The 100% recommended dose is Urea 100 kg/ha, SP-36 150 kg/ha, and KCl 75 kg/ha. The experimental results showed that the application of N fertilizer gave results that had a real effect.  This research can be used as a reference to determine the optimum dose of N fertilization in bambara groundnut cultivation, namely with a dose of Urea 100 kg/ha, SP-36 150 kg/ha, and KCl 75 kg/ha.